A 26-Week Toxicity Assessment of AIR001 (Sodium Nitrite) by Inhalation Exposure in Rats and by Intravenous Administration in Dogs. (May 2014) - Tepper, Jeffrey; Ochoa, Ricardo; Rix, Peter; Elliott, Gary; Hoglen, Niel; Poulin, Dominic; Parsley, Ed; Masamune, Hiroko
Historically, nitrogen oxides (NOx ) in food, drinking water, as well as in the atmosphere have been believed to be associated with adverse health consequences. More recently, NOx have been implicated in normal homeostatic regulation, and exogenous administration has been associated with health benefits. One such potential health benefit is the prospect that inhaled nitrite will lower pulmonary blood pressure (BP) in patients with pulmonary arterial hypertension (PAH), a disease with poor prognosis due to the lack of effective treatment. To characterize potential chronic toxicity associated with inhaled AIR001 (sodium nitrite) for use in the treatment of PAH, 26-week exposures to AIR001 were carried out by inhalation administration in rats and by intravenous infusion in dogs. The studies revealed that methemoglobinemia was the primary adverse effect in both species. Methemoglobin levels less than 40% were well tolerated in both species, while levels greater than 50% methemoglobin caused death in some rats. Additionally, a decrease in systemic BP was also observed with inhaled AIR001 exposure in dogs. These acute secondary and exaggerated pharmacological effects occurred daily throughout the 26-week treatment period. Chronic exposure did not alter the magnitude of either methemoglobinemia or hypotension or result in additional toxicity or compensatory responses. Based on the exposure levels that produced these pharmacodynamic responses in animals, relative to those measured in early clinical studies, it appears that an adequate margin of safety exists to support the continued clinical development of inhaled AIR001.